Crowdsourcing in the Public Sector - Brabham, Daren C., 1982- (Book collections on Project MUSE., 2015)
Crowdsourcing is a term that was coined in 2006 to describe how the commercial sector was beginning to outsource problems or tasks to the public through an open call for solutions over the internet or social media. Crowdsourcing works to generate new ideas or develop innovative solutions to problems by drawing on the wisdom of the many rather than the few. U.S. local government experimented with rudimentary crowdsourcing strategies as early as 1989, but in the last few years local, state, and federal government have increasingly turned to crowdsourcing to enhance citizen participation in problem solving, setting priorities, and decisionmaking. While crowdsourcing in the public sector holds much promise and is part of a larger movement toward more citizen participation in democratic government, there are also many challenges, especially legal and ethical issues, that need to be addressed to successfully adapt it for use in the public sector. This book offers both a scholarly introduction to crowdsourcing in the public sector and a practical "how-to" manual. It includes extensive interviews and concludes with a list of the top ten best practices for public managers.